Antioxidant effect of xanthinyl-7-acetic acid derivative on sod activity under condition of nitrosative stress in vitro - Belenichev, I. F.; Aleksandrova, Katherine V.; Buhtiyarova, Nina V.; Levich, Sergii V.; Nosach, Svitlana G.; Sinchenko, Darja N.; Бєленічев, Ігор Федорович; Александрова, Катерина Вячеславівна; Бухтіярова, Ніна Вікторівна; Левіч, Сергій Вадимович; Носач, Світлана Григорівна; Сінченко, Дар'я Миколаївна (Bulgaria: Hikari Ltd, 2016)
During recent years NO and ONOO– are considered to be a key patho-physiological factor of some basic diseases of the central nervous system (ische-mia, stroke, neurodegenerative diseases, etc.). Therefore search for antioxidants which would reduce NO and ONOO– toxicity seems to be very topical nowadays. In this study, we provide experimental evidence of antioxidant activity of the hy-drazide of Obtained results showed that compound C-3 had pronounced antioxidant properties in conditions of nitrosative stress modeling and caused protective effect on SOD activity. This is the experimental rationale of further investigation of C-3 compound properties in vivo as potential antioxidant. 8-benzylaminotheophyllinyl-7-acetic acid (C-3 compound) (synthe-sized at Department of Biological Chemistry, Zaporozhye State Medical Universi-ty, Zaporozhye, Ukraine). The investigation was conducted in vitro in the test of NO formation. Au-thors suggest that inactivation of superoxide dismutase (SOD) under condition of nitrosative stress plays an important role. We studied effect of C-3 compound on SOD activity under condition of excessive NO and ONOO–production. NO in-duction was performed under the action of light on sodium nitroprusside Na2[Fe(NO)(CN)5]2H2O. The investigation of substances was carried out in su-pernatant obtained from the brain of white Wistar rats (male, 200-250 g). For ni-trosive stress modeling dinitrosyl-Fe2+ cystein complex was utilized.
Keywords: nitric oxide; sodium nitroprusside; superoxide dismutase; theophyl-linyl-7-acetic acid derivative